2011
DOI: 10.1128/aem.02349-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spatial Differences in Microbial Activity, pH, and Substrate Levels on Methanogenesis Initiation in Refuse

Abstract: The initiation of methanogenesis in refuse occurs under high volatile fatty acid (VFA) concentration and low pH (5.5 to 6.25), which generally are reported to inhibit methanogenic Archaea. One hypothesized mechanism for the initiation of methanogenesis in refuse decomposition is the presence of pH-neutral niches within the refuse that act as methanogenesis initiation centers. To provide experimental support for this mechanism, laboratory-scale landfill reactors were operated and destructively sampled when meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 31 publications
3
65
0
2
Order By: Relevance
“…Therefore, some active aeration into these zones would be required for further CH 4 mitigation. Compared to the water content, the other physical and chemical parameters that might have affected the methanogen composition, such as the C/N ratio or pH (Staley et al 2011), were not significantly different between the experimental and control piles, and thus these parameters would not have made a significant contribution and would not have been the reason for the CH 4 mitigation in the manure compost. On the other hand, the CH 4 mitigation obtained in this study could also be explained by the enhancement of CH 4 oxidation occurring in the pile surface zone.…”
Section: Ch 4 Mitigationmentioning
confidence: 99%
“…Therefore, some active aeration into these zones would be required for further CH 4 mitigation. Compared to the water content, the other physical and chemical parameters that might have affected the methanogen composition, such as the C/N ratio or pH (Staley et al 2011), were not significantly different between the experimental and control piles, and thus these parameters would not have made a significant contribution and would not have been the reason for the CH 4 mitigation in the manure compost. On the other hand, the CH 4 mitigation obtained in this study could also be explained by the enhancement of CH 4 oxidation occurring in the pile surface zone.…”
Section: Ch 4 Mitigationmentioning
confidence: 99%
“…Another genus of acetoclastic methanogens, Methanosarcina, is often abundant in methanogenic soils and sediments (23)(24)(25), coal mines (26,27), landfills (28), and anaerobic digesters (29,30). Several studies suggested that Methanosarcina species could accept electrons from nonbiological extracellular surfaces (31,32).…”
mentioning
confidence: 99%
“…The VS c conversion degree in our reactor system was in a similar range like that in comparable two-phase systems (Cysneiros et al 2008), but lower than in one-phase CSTR with maize silage monodigestion (Mähnert 2007). This could be due to spatial differences in percolation systems which can result in inhomogeneous microbial activity and inadequate substrate degradation (Staley et al 2011). Consequently, stirred systems prevail compared to solid-state digesters in full-scale AD of energy crops showing that high-performance hydrolysis and efficient methanogenesis are not mutually exclusive when running simultaneously in one reactor.…”
Section: Discussionmentioning
confidence: 46%